PWE-161 Sessile Serrated Adenomas, Under-Recognised Endoscopically and Under Diagnosed Pathologically. (4th June 2013) - Rafferty, H; Gill, P; Davis, H; Bailey, A; East, J; Chetty, R; Leedham, S
Abstract : Introduction: The serrated pathway of colorectal carcinogenesis is a distinct and important pathway leading to CpG island methylated phenotype (CIMP) carcinomas. These lesions are over-represented in interval cancers and may explain the failure to prevent right-sided cancer with colonoscopy. Hyperplastic polyps (HPs) in the left colon rarely transform whereas proximal serrated adenomas (SSAs) have definite malignant potential and are notoriously difficult to detect endoscopically. There is still uncertainty surrounding the diagnostic criteria and management implications of SSA's, however as pre-malignant lesions it is vital to find, resect and diagnose them. We assessed SSA diagnosis over 4 years in a teaching hospital, and assessed the (epi)genetic mutation burden and expression profile of rectal HPs versus proximal SSAs to see if identifiable molecular differences contribute to their contrasting malignant potential. Methods: We searched the pathology archives from 2009 to 2012 for the diagnosis of serrated adenomas. Cases were reviewed by 2 GI pathologists. Colonoscopic follow up for each case was assessed and compared with new American guidelines 1. 5 distal HP and proximal SSA samples were obtained endoscopically, individual crypts were dissected and morphogen gene expression analysed. Obtained DNA was assessed for BRAF and KRAS mutation and CIMP status by methylight. Results: There were no serrated lesions diagnosed in 2009 - this was an unrecognised entity in our hospital at the time. Of 486 'hyperplastic' polyps diagnosed in 2009, 60 proximal lesions were reassessed and 19 were confirmed as SSAs. In 2010, 40 cases of SSA were diagnosed, rising to 84 in 2011 and 130 in 2012. Follow up of SSAs was appropriate in the majority of cases but lesions aberrantly denoted as hyperplastic in 2009 did not all have follow up arranged at the time. Molecular assessment showed a significant difference in (epi)mutation burden and morphogen gene expression between distal hyperplastic polyps and proximal SSA's. Conclusion: In our hospital there was no distinction made between hyperplastic and serrated lesions prior to 2010. A 3-fold increase in SSA diagnosis in the following 3 years reflects improved endoscopic detection and pathologist recognition of these lesions. The molecular difference between distal HPs and SSAs underpins the proximal predilection of CIMP cancers, and may reflect underlying differences in colonic regional microenvironment, microbiome or morphogen balance. Improved recognition of subtle endoscopic and morphological characteristics of SSAs by gastroenterologists and pathologists will improve colonoscopic surveillance. Disclosure of Interest: None Declared. Reference: Rex DK et al. Am J Gastroentero l 2012; 107(9):1315–29.